Global Financial Stability Report, April 2020 : Markets in the Time of COVID-19. (Global Financial Stability Report; Global Financial Stability Report ;, 2020)
The April 2020 Global Financial Stability Report (GFSR) assesses the financial stability challenges posed by the coronavirus (COVID-19) pandemic. Chapter 1 describes how financial conditions tightened abrubtly with the onset of the pandemic, with risk asset prices dropping sharply as investors rushed to safety and liquidity. It finds that a further tightening of financial conditions may expose vulnerabilities, including among nonbank financial institutions, and that bank resilience may be tested if economic and financial market stresses rise. Vulnerabilities in global risky corporate credit markets, including weakened credit quality of borrowers, looser underwriting standards, liquidity risks at investment funds, and increased interconnectedness, could generate losses at nonbank financial institutions in a severe adverse scenario, as discussed in Chapter 2. The pandemic led to an unprecedented and sharp reversal of portfolio flows, highlighting the challenges of managing flows in emerging and frontier markets. Chapter 3 shows that global financial conditions tend to influence portfolio flows more during surges than in normal times, that stronger domestic fundamentals can help mitigate outflows, and that greater foreign participation in local currency bond markets may increase price volatility where domestic markets lack depth. Beyond the immediate challenges of COVID-19, Chapter 4 explores the profitability pressures that banks are likely to face over the medium term in an environment where low interest rates are expected to persist. Chapter 5 takes a broader perspective on physical risks associated with climate change. It finds that these risks do not appear to be reflected in global equity valuations and that stress testing and better disclosure of exposures to climatic hazards are essential to better assess physical risk.